The Implementation of ISO 14001 In Developed Countries: Literature Review - Anggi Liani, Astisa; Dhiyaulhaq, Arifqah (VISIKES, 2025)
Background: The implementation of ISO 14001 has become increasingly important in addressing global challenges related to sustainability and environmental management. Developed countries have demonstrated strong commitment to this standard as a means to enhance environmental performance, operational efficiency, and industrial competitiveness. Objective: This article explores the similarities and differences among various studies regarding the impact of ISO 14001 implementation, with a focus on both environmental and economic benefits. Methods: This study employed a qualitative descriptive method through a literature review guided by the PRISMA framework. Articles were sourced from Google Scholar using keywords related to ISO 14001, and were then screened and selected based on predefined inclusion and exclusion criteria. Out of 1,650 articles initially identified, 16 were selected for further analysis. Results: The findings indicate that ISO 14001 generally contributes positively to carbon emission reduction and profitability improvement, particularly in countries with high environmental awareness. These studies also emphasize the importance of contextual factors such as company size, market pressure, and national culture in determining the effectiveness of certification. Although most studies employed quantitative methodologies, there was variation in geographical and industrial focus, as well as in adoption motivations, ranging from export advantages to internal company improvements. Conclusion: The success of ISO 14001 implementation is not universal and depends on the specific conditions of each company and country. Therefore, a more tailored approach and adequate policy support are necessary to encourage broader and more effective adoption of this standard.